The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/bmc.5155
|View full text |Cite
|
Sign up to set email alerts
|

Application of experimental design in HPLC method optimization and robustness for the simultaneous determination of canagliflozin, empagliflozin, linagliptin, and metformin in tablet

Abstract: Gliflozins and gliptins represent two different pharmacological drug classes that exert different and potentially complementary glucose-lowering effect in patients with type II diabetes mellitus. A novel, selective, and sensitive HPLC method was developed for the determination of canagliflozin, empaglifozin, linagliptin, and metformin in pure form, in laboratory prepared mixtures, and in pharmaceutical dosage form. Experimental design optimization was applied by using Plackett-Burman and face-centered composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Separation quality is important; thus, the typical key response is good resolution between critical analyte peaks [ 56 , 57 , 58 ]. Similar work has been reported on different drugs in which the resolution was the only response, while buffer pH, percentage acetonitrile, and flow rate had a significant effect on the response [ 51 , 52 , 53 , 58 ]. The three-level face-centered central composite design suggested by the software and the resolution results are tabulated below ( Table 1 ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Separation quality is important; thus, the typical key response is good resolution between critical analyte peaks [ 56 , 57 , 58 ]. Similar work has been reported on different drugs in which the resolution was the only response, while buffer pH, percentage acetonitrile, and flow rate had a significant effect on the response [ 51 , 52 , 53 , 58 ]. The three-level face-centered central composite design suggested by the software and the resolution results are tabulated below ( Table 1 ).…”
Section: Resultssupporting
confidence: 75%
“…The quadratic effect of acetonitrile concentration, pH, and flow rate had a substantial impact on the resolution between RE and VD, whereas only acetonitrile concentration and pH exhibited a substantial effect on the resolution between VD and MF. The reported methods for the optimization of chromatographic conditions for the separation of metformin with other drugs showed a much lower effect due to the use of RP-HPLC, where metformin was eluted first [ 52 , 53 ]. The assessed model F -values were found to be 26.06 and 33.40 ( p < 0.0001) for RS1 and RS2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review of the available literature found that a number of analytical techniques, such as spectrophotometric [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], colorimetric [ 31 , 32 , 33 ], spectrofluorometric [ 33 , 34 , 35 ], and high-performance liquid chromatographic [ 36 , 37 , 38 , 39 ] methods, were described for the detection of linagliptin. It has been determined that colorimetric is more specific than spectrophotometry (UV region).…”
Section: Introductionmentioning
confidence: 99%
“…DN has an insidious onset, which progresses rapidly by the proteinuria stage in the clinic, with symptoms such as edema, dyslipidemia, and continuous decline in renal function. However, conventional hypoglycemic agents are limited in DN treatment, and most oral hypoglycemic agents cannot be used in stages 3-4 of chronic kidney disease (CKD) [4][5][6]. In contrast, as a new type of a dipeptidyl peptidase 4 (DPP-4) inhibitor, linagliptin tablets can be excreted through the intestine and can be used even in patients with renal insufficiency or on dialysis, with a good hypoglycemic effect.…”
Section: Introductionmentioning
confidence: 99%